Consumer Ethics: The Role of Religiosity - Vitell, Scott J. (Journal of business ethics, 2003)
This article presents the results of a study that investigated the role that religiosity plays in determining consumer attitudes/beliefs regarding various questionable consumer practices. Additionally, other personal factors were examined including idealism, relativism, consumer alienation and selected demographics such as income and age. All of these constructs were examined as antecedents of consumer ethical beliefs. The results of a post hoc analysis indicated that religiosity was a significant determinate of both idealism and relativism, and since idealism and relativism determine consumer ethical beliefs, religiosity is a significant indirect determinate of consumer ethical beliefs.